2023
DOI: 10.3390/v15040954
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamic of the Ratio between Monopartite Begomoviruses and Their Associated Betasatellites in Plants, and Its Modulation by the Viral Gene βC1

Abstract: The begomovirus–betasatellite complex constantly threatens crops in Asia. However, the quantitative relationship between begomoviruses and betasatellites remains largely unknown. The quantities of tobacco curly shoot virus (TbCSV) and its betasatellite (TbCSB) and their ratio varied significantly in initial infection, and thereafter, the ratio tended to become constant. The TbCSB/TbCSV ratio in agrobacteria inoculum significantly affected that in plants in the initial infection but not thereafter. Null-mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In plants infected with tobacco curly shoot virus (TbCSV) and its betasatellite (TbCSB), the amount of TbCSB is higher at the initial stages of infection, and becomes constant at a later stage of infection. It was shown that a higher TbCSB/TbCSV ratio promotes transmission of the virus by the vector whitefly [ 52 ]. The efficiency of transmission of five different begomoviruses by the vector whitely was found to vary from virus to virus; similarly, in the vector transmission of beta- and alphasatellites, transmission efficiency by four different cryptic species of whiteflies have also been shown to vary [ 35 ].…”
Section: Role Of Betasatellites In Transmission Of Begomoviruses By ...mentioning
confidence: 99%
“…In plants infected with tobacco curly shoot virus (TbCSV) and its betasatellite (TbCSB), the amount of TbCSB is higher at the initial stages of infection, and becomes constant at a later stage of infection. It was shown that a higher TbCSB/TbCSV ratio promotes transmission of the virus by the vector whitefly [ 52 ]. The efficiency of transmission of five different begomoviruses by the vector whitely was found to vary from virus to virus; similarly, in the vector transmission of beta- and alphasatellites, transmission efficiency by four different cryptic species of whiteflies have also been shown to vary [ 35 ].…”
Section: Role Of Betasatellites In Transmission Of Begomoviruses By ...mentioning
confidence: 99%